ISLAM DAN PENDIDIKAN MULTIKULTURAL - Haryati, Tri Astutik (TADRIS: Jurnal Pendidikan Islam, 2009)
The core of multiculturalism is the willingness to receive other groups as an equal and united part. It denies cultural, ethnical, gender, language and religious distinctions. Multiculturalism becomes a contextual idea relating to the current contemporary society. The basic priciples of equity, justice, openness, and difference recognition are the value principle needed by human in the crush of global culture. Thus, education has been an appropriate media to establish emulticultural. As a result, it is urgently required to design a curriculum of multicultural education containing some materials that are able to present multiperspectives of certain cultural phenomena.